2020
DOI: 10.18488/journal.aefr.2020.101.54.63
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Corporate Governance on Financial Institutions’ Performance: A Board Composition Case

Abstract: The impact and implementation of Corporate Governance (CG) has been a matter of interest for various firms, as it substantially affects the financial stability of institutions. This study analyses the impact of Corporate Governance (CG) elements that include board composition on the financial performances of the financial institutions listed on Jordan"s Amman Stock Exchange (ASE). The study population involved 40 Jordanian financial institutions belonging to both commercial banks and financial companies listed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 20 publications
1
21
0
1
Order By: Relevance
“…Hal ini karena terjadinya banyak skandal keuangan dan akuntansi akibat lemahnya CG di banyak perusahaan. Enron adalah salah satu contoh nyata akibat lemahnya tata kelola perusahaan yang mengakibatkan kegagalan keuangan (Bawaneh, 2020). Kegagalan Enron telah menyebabkan meningkatnya permintaan untuk CG yang lebih baik.…”
Section: Corporate Governanceunclassified
“…Hal ini karena terjadinya banyak skandal keuangan dan akuntansi akibat lemahnya CG di banyak perusahaan. Enron adalah salah satu contoh nyata akibat lemahnya tata kelola perusahaan yang mengakibatkan kegagalan keuangan (Bawaneh, 2020). Kegagalan Enron telah menyebabkan meningkatnya permintaan untuk CG yang lebih baik.…”
Section: Corporate Governanceunclassified
“…Latest assertions concerning the transition to the knowledgebased economy have strengthened the call to institutional ideas. Conceptions about creativity as a socially equitable and collaborative mechanism have contributed to new arguments regarding the value of localized learning in the creation of strategic regional advantage (Bawaneh, 2020;Commission, 2019;Munusamy & Wong, 2007). The main point is that in particular, the transfer of implicit information types involves regular social contact and consequently near geographical proximity between companies contributing to new forms of spatial clustering in knowledge-based industries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The result of the study will help the bank of Ghana and ARB Apex Bank to form a corporate governance framework in rural banks. (Bawaneh, 2020) explained how the impact and implementation of corporate governance elements affect the financial stability of financial institutions and suggested that to analyze the institution's performance all corporate governance factors should be considered. (Bezawada & Adavelli, 2020) investigated the set of board characteristics and analyzed the impact of the board characteristics on asset quality and performance of the banks.…”
Section: Literature Reviewmentioning
confidence: 99%